2014
DOI: 10.1007/s11356-014-3347-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal variation in particulate matter (PM10 and PM2.5) at an urban site of Beijing: analyses from a 9-year study

Abstract: Air pollution has become a top environmental concern in China. In the present study, 9 years of PM10 and PM2.5 data from an urban monitoring station in Beijing was analyzed relative to other gaseous pollutants and several meteorological parameters. The levels and characteristics of particulate matters as well as the sources and factors affecting them were provided in the present study. During the 9-year observation period, PM10 and PM2.5 showed high levels, with annual mean values of 138.5 ± 92.9 and 72.3 ± 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(114 citation statements)
references
References 70 publications
13
97
2
2
Order By: Relevance
“…Several studies [37,38] found positive relationships between PM and temperature. This occurs because warm weather induces the formation of secondary fine particles, therefore increased temperatures result in increased PM [39,40]. PM was negatively correlated with relative humidity in spring.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [37,38] found positive relationships between PM and temperature. This occurs because warm weather induces the formation of secondary fine particles, therefore increased temperatures result in increased PM [39,40]. PM was negatively correlated with relative humidity in spring.…”
Section: Discussionmentioning
confidence: 99%
“…These enhancements include plots being shown as a continuous surface and surfaces being calculated through modeling using smoothing techniques. These plots are not entirely new as others have considered the joint wind speed-direction dependence of concentrations (see for example Liu et al, 2015). However, plotting the data in polar coordinates and for the purposes of source identification is new.…”
Section: Conditional Probability Function and Bivariate Polar Plot Fomentioning
confidence: 99%
“…These enhancements include: plots are shown as a continuous surface and surfaces are calculated through modelling using smoothing techniques. These plots are not entirely new as others have considered the joint wind 305 speed-direction dependence of concentrations (see for example Liu et al (2015)). …”
Section: Discussionmentioning
confidence: 97%